A two-component system (XydS/R) controls the expression of genes encoding CBM6-containing proteins in response to straw in Clostridium cellulolyticum. - Hamza Celik; Jean-Charles Blouzard; Birgit Voigt; Dörte Becher; Valentine Trotter; Henri-Pierre Fierobe; Chantal Tardif; Sandrine Pagès; Pascale de Philip (PLoS ONE, 2013)
The composition of the cellulosomes (multi enzymatic complexes involved in the degradation of plant cell wall polysaccharides) produced by Clostridium cellulolyticum differs according to the growth substrate. In particular, the expression of a cluster of 14 hemicellulase-encoding genes (called xyl-doc) seems to be induced by the presence of straw and not of cellulose. Genes encoding a putative two-component regulation system (XydS/R) were found upstream of xyl-doc. First evidence for the involvement of the response regulator, XydR, part of this two-component system, in the expression of xyl-doc genes was given by the analysis of the cellulosomes produced by a regulator overproducing strain when grown on cellulose. Nano-LC MS/MS analysis allowed the detection of the products of all xyl-doc genes and of the product of the gene at locus Ccel_1656 predicted to bear a carbohydrate binding domain targeting hemicellulose. RT-PCR experiments further demonstrated that the regulation occurs at the transcriptional level and that all xyl-doc genes are transcriptionally linked. mRNA quantification in a regulator knock-out strain and in its complemented derivative confirmed the involvement of the regulator in the expression of xyl-doc genes and of the gene at locus Ccel_1656 in response to straw. Electrophoretic mobility shift assays using the purified regulator further demonstrated that the regulator binds to DNA regions located upstream of the first gene of the xyl-doc gene cluster and upstream of the gene at locus Ccel_1656.